2008
DOI: 10.1051/parasite/2008151077
|View full text |Cite
|
Sign up to set email alerts
|

Infection of foxes byEchinococcocus multilocularisin urban and suburban areas of Nancy, France: influence of feeding habits and environment

Abstract: Summary :This study evaluated the impact of biological and environmental factors on the infection of red foxes (Vulpes vulpes) by Echinococcus multilocularis in an endemic area of north-east France. From January 2004 to April 2006, 127 foxes were examined for E. multilocularis and their stomach contents analysed. The effect of year, season, age, sex and urbanisation level on E. multilocularis presence was estimated using a General Linear Model (GLM) with logit link, (i.e. logistic regression). Urbanisation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
(35 reference statements)
2
46
0
2
Order By: Relevance
“…A general pattern that seems to emerge is a decrease in E. multilocularis prevalence in foxes according to the following gradient: rural periphery/residential peri-urban area/urban centre. The distribution of intermediate host populations has been investigated in Zurich and Nancy (Hegglin et al, 2007;Robardet et al, 2008) with similar findings (see Table 2 for a comparison between Zurich and Nancy cities, where key ecological parameters of the cycles have been documented). Indeed, one of the main fox prey species displayed a higher density in the rural periphery (M. arvalis in Nancy) and/or in the residential peri-urban area (A. scherman in Zurich) compared to the urban centre where the relative densities of both prey species were lower due to reduced availability of suitable habitats (grasslands) and the lower numbers of animals within these habitats.…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 72%
See 3 more Smart Citations
“…A general pattern that seems to emerge is a decrease in E. multilocularis prevalence in foxes according to the following gradient: rural periphery/residential peri-urban area/urban centre. The distribution of intermediate host populations has been investigated in Zurich and Nancy (Hegglin et al, 2007;Robardet et al, 2008) with similar findings (see Table 2 for a comparison between Zurich and Nancy cities, where key ecological parameters of the cycles have been documented). Indeed, one of the main fox prey species displayed a higher density in the rural periphery (M. arvalis in Nancy) and/or in the residential peri-urban area (A. scherman in Zurich) compared to the urban centre where the relative densities of both prey species were lower due to reduced availability of suitable habitats (grasslands) and the lower numbers of animals within these habitats.…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 72%
“…The urban cycle of the parasite is now documented in Zurich and Geneva (Switzerland), Stuttgart (Germany), Copenhagen (Denmark), Sapporo (Japan), Nancy, Annemasse and Pontarlier (France), and Calgary (Canada) (Hofer et al, 2000;Tsukada et al, 2000;Deplazes et al, 2004;Fischer et al, 2005;Robardet et al, 2008;Catalano et al, 2012;Comte et al, 2013). A general pattern that seems to emerge is a decrease in E. multilocularis prevalence in foxes according to the following gradient: rural periphery/residential peri-urban area/urban centre.…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the environmental contamination by infectious free-living stages, and thereafter the infection pressure by these parasites, is likely to differ and depend on the distribution, abundance and habitat use of the respective definitive hosts, notably in urbanized areas. High prevalences of infection with T. canis in domestic dogs and red foxes in urban areas (O'Lorcain, 1994 ;Habluetzel et al 2003 ;Reperant et al 2007), and high prevalences of infection with E. multilocularis in red foxes in peri-urban areas (Hofer et al 2000 ;Fischer et al 2005 ;Robardet et al 2008) have notably been reported, suggesting high levels of environmental contamination in these environments.…”
Section: Introductionmentioning
confidence: 99%